Tatalaksana Vitiligo - Caryn Miranda Saptari (Cermin Dunia Kedokteran, 2019)
Vitiligo merupakan kelainan depigmentasi kulit yang ditandai dengan lesi klinis makula atau plak depigmentasi berbatas tegas, diperkirakan karena faktor imun, genetik, disfungsi sekunder dan kehilangan melanosit. Terdapat 3 tipe vitiligo : vitiligo segmental (VS), vitiligo non-segmental (NSV) dan vitiligo campuran. Penatalaksanaan vitiligo secara medikamentosa dan non – medikamentosa. Vitiligo is a skin disease characterized by a clinically well-defined macular or depigmented plaque; may be due to immune factors, genetics, secondary dysfunction and loss of melanocytes. There are 3 types of vitiligo: segmental vitiligo (VS), non-segmental vitiligo (NSV) and mixed vitiligo. Management of vitiligo is generally divided into medical treatment and procedural treatments.